2003
DOI: 10.1074/jbc.m209442200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of the RNA Polymerase β Subunit Flap Domain in ς54-Dependent Transcription

Abstract: Recent determinations of the structures of the bacterial RNA polymerase (RNAP) and promoter complex thereof establish that RNAP functions as a complex molecular machine that contains distinct structural modules that undergo major conformational changes during transcription. However, the contribution of the RNAP structural modules to transcription remains poorly understood. The bacterial core RNAP (␣ 2 ␤␤; E) associates with a sigma () subunit to form the holoenzyme (E Multisubunit DNA-dependent RNA polymerases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…However, both 54 -and 54 -RNAP bind equally well to the early melted promoter probe (12,37,40). We previously demonstrated that the RNAP ␤-subunit flap domain contributes (either directly or indirectly) to the creation of the DNA fork junction at the Ϫ12 promoter region (31). We propose that during closed complex formation, 54 Region I and promoter DNA undergo core RNAP-directed conformational changes involving the ␤-subunit flap domain that result in (i) creation of the DNA fork junction at the Ϫ12 promoter region and (ii) the tight binding of the 54 Region I to the DNA fork junction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both 54 -and 54 -RNAP bind equally well to the early melted promoter probe (12,37,40). We previously demonstrated that the RNAP ␤-subunit flap domain contributes (either directly or indirectly) to the creation of the DNA fork junction at the Ϫ12 promoter region (31). We propose that during closed complex formation, 54 Region I and promoter DNA undergo core RNAP-directed conformational changes involving the ␤-subunit flap domain that result in (i) creation of the DNA fork junction at the Ϫ12 promoter region and (ii) the tight binding of the 54 Region I to the DNA fork junction.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli core RNAP containing the ␤-subunit flap deletion (⌬885-914) was purified as described in Ref. 31. Wild-type E. coli core RNAP was purchased from Epicentre Technologies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6c). Binding of 54 or 54 -RNAP to the S. meliloti nifH homoduplex probe or probe 1 (Table Ia) response to ATP hydrolysis by the activator (11,14,19).…”
Section: Action Of Pspf 1-275 -Atp␥s and Pspf 1-275 -Atp␥s/atp On 54 mentioning
confidence: 99%
“…OP-Cu is a minor groove-specific DNA cleaving reagent that has been widely used to study 54 -RNAP interactions with the Ϫ12 promoter region (6,19). In closed promoter complexes formed with the 54 -RNAP on homoduplex promoter probe (Table Ia), the minor groove at the Ϫ12 position is distorted and thus is susceptible to cleavage by OP-Cu (6).…”
Section: Binding Of Trapped 54 and 54 -Rnap To Promoter Probe 2 Leadsmentioning
confidence: 99%